Management of sulfonylurea‐treated monogenic diabetes in pregnancy: implications of placental glibenclamide transfer. Issue 10 (13th June 2017) - Shepherd, M.; Brook, A. J.; Chakera, A. J.; Hattersley, A. T.
Abstract: The optimum treatment for HNF1A/HNF4A maturity‐onset diabetes of the young and ATP‐sensitive potassium (KATP ) channel neonatal diabetes, outside pregnancy, is sulfonylureas, but there is little evidence regarding the most appropriate treatment during pregnancy. Glibenclamide has been widely used in the treatment of gestational diabetes, but recent data have established that glibenclamide crosses the placenta and increases risk of macrosomia and neonatal hypoglycaemia. This raises questions about its use in pregnancy. We review the available evidence and make recommendations for the management of monogenic diabetes in pregnancy. Due to the risk of stimulating increased insulin secretion in utero, we recommend that in women with HNF1A/ HNF4A maturity‐onset diabetes of the young, those with good glycaemic control who are on a sulfonylurea per conception either transfer to insulin before conception (at the risk of a short‐term deterioration of glycaemic control) or continue with sulfonylurea (glibenclamide) treatment in the first trimester and transfer to insulin in the second trimester. Early delivery is needed if the fetus inherits an HNF4A mutation from either parent because increased insulin secretion results in 800‐g weight gain in utero, and prolonged severe neonatal hypoglycaemia can occur post‐delivery. If the fetus inherits a KATP neonatal diabetes mutation from their mother they have greatly reduced insulin secretion in utero that reduces fetal growth by 900 g. Treating the mother with glibenclamide in the third trimester treats the affected fetus in utero, normalising fetal growth, but is not desirable, especially in the high doses used in this condition, if the fetus is unaffected. Prospective studies of pregnancy in monogenic diabetes are needed. What's new?: Recent data show that glibenclamide crosses the placenta and its use in pregnancy is associated with increased birth weight and neonatal hypoglycaemia. This has implications for the treatment of pregnant women with monogenic diabetes whose diabetes is usually well controlled with sulfonylureas. Optimum management of HNF1A/HNF4A maturity‐onset diabetes of the young (MODY) in pregnancy requires excellent glycaemic control in the first trimester to minimize the risk of fetal malformations, whilst avoiding the negative impact of glibenclamide on fetal weight gain in the third trimester. In mothers with ATP‐sensitive potassium channel (KATP ) neonatal diabetes, glibenclamide treatment in pregnancy can be beneficial if the fetus is affected because restoration of fetal KATP function will result in improved fetal growth. If the genotype of the fetus is unknown, when a parent has KATP neonatal diabetes or HNF4A MODY, serial antenatal ultrasound assessment of fetal growth may be used as a proxy to aid management decisions. Management of monogenic diabetes during pregnancy could be revolutionized in future by testing cell‐free fetal DNA in the mother.